Proceedings of the 2017 7th International Conference on Education, Management, Computer and Society (EMCS 2017) 2017
DOI: 10.2991/emcs-17.2017.133
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation Analysis of Design Code About the Road Design of longitudinal gradient in the Mountain Road

Abstract: Abstract. In recent years the highway develops rapidly in China, by the end of 2014, the total mileage of China's highway has reached 4.3 million kilometers. Among those, the total mileages of the speedway broke through the bottleneck of 110 thousand kilometers -which ranks the first in the world. With the fast development of basic traffic construction, the problem of safety has become more and more significant. However, some highway (especially, the long longitudinal gradient in the mountain area) has the hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…e main reason for exceeding speed limits, by some authors, refers to the credibility of set speed limits because drivers do not consider them realistic [18][19][20]. However, some authors have investigated the functional dependence of speed, length of individual geometric elements of the road, radius of curvature, transverse/longitudinal gradient, and traffic accidents [21][22][23][24]. Also, the research presents the problem of reducing speed due to the geometric characteristics of the road.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…e main reason for exceeding speed limits, by some authors, refers to the credibility of set speed limits because drivers do not consider them realistic [18][19][20]. However, some authors have investigated the functional dependence of speed, length of individual geometric elements of the road, radius of curvature, transverse/longitudinal gradient, and traffic accidents [21][22][23][24]. Also, the research presents the problem of reducing speed due to the geometric characteristics of the road.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the analysis of the Bayesian network for predicting the probability of the influence of traffic and road factors on the occurrence of traffic accidents, the following are especially emphasized: vehicle speed, horizontal curve radius, vehicle type, adhesion coefficient, and longitudinal slope [23]. Also, the results of a study [24] show that the continuous use of several limit indexes and the excessive average slope of long and steep sections of roads were one of the major causes of frequent 2 Complexity accidents on a section of HeXi road in China. In their study, Silvano et al assessed the impact of technical and exploitation characteristics of the road and changes in speed limits on the speed of free traffic flow using an extensive dataset of urban roads [28].…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, some authors have investigated the functional dependence of speed, length of individual geometric road elements, radius of curvature of transverse/longitudinal slopes, and traffic accidents [9][10][11][12]. Additionally, in some research the problem of reducing speed due to geometric road characteristics arises.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Using the Bayesian network analysis for predicting the probability of the influence of traffic and road factors on the occurrence of traffic accidents, it is especially emphasized that vehicle speed, horizontal curve radius, vehicle type, adhesion coefficient, and longitudinal slope are important factors [11]. Additionally, the results of the study [12] show that the continuous use of several boundary indices and the excessive average gradient of long and steep road sections are some of the main causes of frequent accidents on the Hexi section.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Wen-bin [5] established traffic simulation models with different actual loading rates and slope lengths through Vissim, and ultimately verified them during the renovation of the long and steep slope of the Expressway. Zheng [6] used the American safety analysis method to estimate the operational safety of long longitudinal slope highways in mountainous areas. The study showed that although the continuous long downhill of these mountain roads did not exceed the limit value, the maximum longitudinal slope length and slope value almost often reached the standard limit.…”
Section: Introductionmentioning
confidence: 99%